Influencia del apoyo familiar en el desempeño académico de los estudiantes del tercer año de educación básica - Baquerizo Hidalgo, Carmen Diana (2025)
This report presents the development, implementation, and evaluation of the educational project titled “Family Support and Its Impact on Academic Performance of Third Grade Students at Unión Empálmense Elementary School, El Empalme, Academic Year 2023– 2024.” The research responds to the growing need to strengthen the relationship between family and school, based on the premise that emotional, academic, and organizational support provided by families has a direct influence on student learning outcomes.